Mppt Control for PV Systems with Analytical Analysis Fractional Open Circuit Voltage Method - Cakmak, Fevzi; Aydogmus, Zafer; Tur, Mehmet Rida (Institute of Electrical and Electronics Engineers Inc., 2022)
In this study, analytical resolved fractional open circuit voltage (FOCV) maximum power point tracking (MPPT) method is presented. The proposed method is obtained by calculating it by utilizing the single diode circuit of the PV module, while measuring the open circuit voltage (Voc) by interrupting the power of other open circuit voltage methods. Vmpp is obtained by multiplying the obtained Voc voltage with the coefficient. The voltage variation (E) is obtained by the subtraction between the panel voltage (Vpv) and the Vmpp voltage. It is applied as an input to the PI controller by multiplying the Ki factor to limit the voltage variation (E). The PI Controller generates the required duty cycle for the DC-DC converter. The most important advantage of this method is acquaring open circuit voltage without power interruption. The proposed method operated effectively at different radiation and temperature values. For the proposed method, it has simulated in Matlab/Simulink program using SHARP NDQ295 model PV panel. © 2022 IEEE.
2022 IEEE Global Energy Conference, GEC 2022 -- 26 October 2022 through 29 October 2022 -- Batman -- 185674
Keywords: analytical resolved FOCV; MPPT; open circuit voltage; Photovoltaic system